EVALUATION OF TYPE 2 DIABETES MELLITUS PATIENTS ATTITUDES TOWARD REPORTING ADVERSE DRUG REACTIONS (ADRS) REGARDING PROLANIS IN THREE PRIMARY HEALTHCARE CENTERS IN BANDUNG CITY - Nurul Islami, Dewi
ADR contributes to the morbidity and mortality rates among drug users. To prevent and detect ADR, a pharmacovigilance system has been developed that involves reporting of ADR by healthcare professionals and patients. Prolanis is a healthcare service system with a proactive approach for patients with chronic diseases such as Diabetes Mellitus (DM) Type 2. Prolanis patients often use one or more drugs regularly, which can increase the risk of ADR. ADR monitoring is crucial for Prolanis patients to achieve optimal quality of life. This study aims to analyze the experiences and knowledge of DM Type 2 patients regarding ADR and its reporting, the attitudes of Prolanis DM Type 2 patients towards ADR, and the reasons patients report ADR to healthcare professionals. The research was conducted in three community health centers in Bandung city, namely Garuda Community Health Center, Sukarasa Community Health Center, and Ibrahim Adjie Community Health Center. This study was conducted observationally with a cross-sectional design using a questionnaire filled out by 102 respondents. The results of the study showed that patients' knowledge of reporting ADR was influenced by their experiences of receiving ADR information (p = 0.008). 66 respondents (65%) had a positive attitude, and 80 respondents (78%) had strong reasons forreporting ADR. From the correlation test results, a significant relationship was found between patients' attitudes towards ADR and their reasonsfor reporting ADR (p = 0.001; r = 0.311). It can be concluded that the experience of receiving ADR information influences the knowledge related to reporting ADR. In addition, the respondents had a relatively positive attitude towards ADR and strong reasons for reporting ADR. Patients' attitudes have a significant correlation with their reasons for reporting ADR.